A Review of Requirements and Approaches for Realistic Visual Perception in Virtual Reality - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
The amount of new virtual reality input and output devices being developed is enormous. Those peripherals offer novel opportunities and possibilities in the industrial context, especially in the product development process. Nevertheless, virtual reality has to face several problems, counteracting reliable use of the technology, especially in ergonomic and aesthetic assessments. In particular, the discrepancies in perception between the real world and virtual reality are of great importance. Therefore, we discuss these most important issues of current virtual reality technology and highlight approaches to solve them. First, we illustrate the use cases of VR in the product development process. In addition, we show which hardware is currently available for professional use and which issues exist with regard to visual perception and interaction. Derived from the depiction of a perfect virtual reality, we define the requirements to address visual perception and interaction. Subsequently we discuss approaches to solve the issues regarding visual perception and evaluate their suitability to enhance the use of virtual reality technology in engineering design.
Keywords: Virtual reality; Visualisation; Visual perception; Eye tracking; Conceptual design

CAD-Gestaltmodellierung in VR für die frühe Entwurfsphase - Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2020)
Virtual Reality bietet neben der stereoskopischen Visualisierung zusätzlich die Möglichkeit der natürlichen Interaktion mit virtuellen Objekten ähnlich der Interaktion mit physischen Objekten in der Realität. Der nachfolgende Beitrag beschreibt eine auf Fingertracking basierende Methode, mit der die Gestalt eines frühen Entwurfs innerhalb einer virtuellen Umgebung in einer CAD-Anwendung synthetisiert werden kann.

Comparative evaluation of WIMP and immersive natural finger interaction: a user study on CAD assembly modeling - Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Virtual Reality, 2021)
Virtual and augmented reality allows the utilization of natural user interfaces, such as realistic finger interaction, even for purposes that were previously dominated by the WIMP paradigm. This new form of interaction is particularly suitable for applications involving manipulation tasks in 3D space, such as CAD assembly modeling. The objective of this paper is to evaluate the suitability of natural interaction for CAD assembly modeling in virtual reality. An advantage of the natural interaction compared to the conventional operation by computer mouse would indicate development potential for user interfaces of current CAD applications. Our approach bases on two main elements. Firstly, a novel natural user interface for realistic finger interaction enables the user to interact with virtual objects similar to physical ones. Secondly, an algorithm automatically detects constraints between CAD components based solely on their geometry and spatial location. In order to prove the usability of the natural CAD assembly modeling approach in comparison with the assembly procedure in current WIMP operated CAD software, we present a comparative user study. Results show that the VR method including natural finger interaction significantly outperforms the desktop-based CAD application in terms of efficiency and ease of use.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Assembly modeling; Computer-aided design; Natural user interface; Virtual reality

Impact of collaborative space on team work in engineering design education - Fechter, Marius; Kett, Susan; Luft, Thomas; Wartzack, Sandro (DS 84: Proceedings of the DESIGN 2016 14th International Design Conference, 2016)
This paper presents a study investigating the impact of space design on behaviour and creative outcome of team work in learning environments. A dedicated space was especially designed and equipped to facilitate creativity during collaboration. A student course in engineering design was held both in conventional classroom settings and in the newly designed space. The observations and measurements made relating to the two environments are shown and discussed in the paper. The results indicate noteworthy differences that can help to positively influence learning and creativity in future lectures.
Keywords: collaboration; space design; creativity; design education

Interactive immersive engineering system for distant collaboration - Fechter, Marius; Damgrave, Roy Gerhardus Johannes; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), 2015)
Complex products consisting of various components are designed in collaboration of multi-disciplinary engineering teams with different expertise. Expert groups involved in the development process are possibly based at geographically distributed locations. The purpose of this contribution therefore is the development of a framework, enhancing the quality of communication and facilitating the exchange of information and expertise in engineering projects over distance. This framework provides the capability to visualise a product model and the avatars of distant people in one shared immersive virtual environment. Furthermore the integration of product information exceeding the pure geometry and features for direct modification of the visualised product are achieved through the connection to CAD software. The intuitive interaction interface utilises hand gestures based on normal physical interaction with real objects. Being able to see both the 3D model and the other participant in one shared virtual environment creates a natural communication and interaction process, without being distracted by new communication or interaction methods forced by the technology.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.intera
Keywords: Collaborative Design; Communication; Human-Computer Interaction; Virtual Reality

Intuitive virtual reality - CAD assembly system - Fechter, Marius; Miehling, Jörg; Stangl, Thomas; Wartzack, Sandro (Proceedings of the DESIGN 2014 13th International Design Conference, 2014)
The application of virtual reality during the design engineering process possesses the potential to experience and to interact with virtual products in a natural and intuitive manner. Some workflows in the field of computer-aided design, like assembling components, exhibit disadvantages that result from the two-dimensional vision and the limitations of common human-computer interaction. To support the design engineer, this paper focuses on developing a framework that harnesses the benefits of intuitive gesture based hand interaction and stereoscopic visualisation.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.intuit
Keywords: virtual reality; computer-aided design; gesture interaction

Konzept für ein VR-System zur intuitiven Modellierung durch natürliche Interaktion - Fechter, Marius; Wartzack, Sandro (Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik, 2016)
Durch den Einsatz von virtueller Realität (VR) eröffnet sich die Möglichkeit zur Entwicklung intuitiver Interaktionsmethoden, die dem Produktentwickler erlauben, natürlich mit den virtuellen Modellen umzugehen. Dazu wird in diesem Beitrag ein System konzipiert, aufgebaut und angewendet mit dem sich Komponenten innerhalb eines CAD-Systems durch Abhängigkeiten zusammenfügen lassen. Dabei werden Verfahren zum markenlosen Finger-Tracking sowie eine aktuelle VR-Brille verwendet. In einer Fallstudie wird abschließend die Anwendbarkeit des Hard- und Softwaresystems demonstriert. Link zu einem Video zur Veröffentlichung: https://vimeo.com/159390784
Keywords: Virtual Reality; CAD; Natural User Interface

Konzept zur Verbesserung des realitätsgetreuen, visuellen Erlebens in virtuellen Umgebungen durch Eye-Tracking - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Entwerfen Entwickeln Erleben in Produktentwicklung und Design 2019, 2019)
Ein positives Nutzungserlebnis (engl. User Experience) ist einer der Schlüsselaspekte erfolgreicher Produkte und damit auch die Grundlage für den wirtschaftlichen Erfolg des Unternehmens. Ergonomische Bedienbarkeit und ansprechende Gestaltung des Produkts haben hierauf einen starken Einfluss. Entwickler und Designer versuchen deshalb, dieses Erlebnis bereits in einer möglichst frühen Phase des Produktenwicklungsprozesses zu erfassen und zu bewerten. Ein in der Automobilbranche erfolgreich eingesetztes Werkzeug zur Bewertung des Nutzererlebnisses ist der Prototypenbau. Der Einsatz von Prototypen ist allerdings mit einem hohen zeitlichen und finanziellen Aufwand verbunden und erst in späteren Phasen des Produktentwicklungsprozesses möglich. Zu diesem Zeitpunkt können Produktänderungen einen hohen zeitlichen und finanziellen Mehraufwand bedeuten. Im Sinne des „Frontloadings“ ist es daher wünschenswert, für die Bewertung des Nutzererlebnisses früh zur Verfügung stehende, digitale Modelle zu nutzen. Damit können frühzeitig erste Erkenntnisse über das Nutzungserlebnis unterschiedlicher Konzepte in die Entwicklung des Produkts einfließen. Durch Einsatz von Methoden der Virtuellen Realität (VR) besteht die theoretische Möglichkeit, eine Bewertung des Produkts hinsichtlich Design und Ergonomie bereits in frühen Phasen des Produktentwicklungsprozesses durchzuführen. Jedoch besteht bei der visuellen Wahrnehmung von Größe, Distanz und Form in einem Head-Mounted Display (HMD), insbesondere im Nahbereich, eine signifikante Diskrepanz zwischen der virtuellen Darstellung eines Modells und dessen realen Aufbaus. Die Ursachen dieser Wahrnehmungsdiskrepanzen konnten in bisherigen empirischen Studien nicht exakt festgestellt werden. Im Allgemeinen werden diese mit fehlenden Tiefenhinweisen oder Abweichungen in zur Berechnung der visuellen Darstellung verwendeten Parametern, wie dem Sichtfeld oder dem Pupillenabstand, erklärt. Als Folge der vorhandenen Diskrepanz zwischen der gewünschten und der erzielten Darstellung, sind Ergebnisse aus virtuellen Studien, insbesondere für die Evaluierung ergonomischer Aspekte wie der Erreichbarkeit einzelner Bedienelemente, nur bedingt belastbar. Bisher verwenden die meisten HMDs eine vereinfachte Modellbildung zur Berechnung der visuellen Darstellung von Objekten. Es wird über die räumliche Lage des Kopfes auf die Positionen der Pupillen geschlossen, anstatt die exakten Pupillenpositionen heranzuziehen. Durch den Einsatz von Eye-Tracking innerhalb von HMD‘s eröffnet sich die Möglichkeit, die genaue Pupillenposition bei der Berechnung der visuellen Darstellung zu berücksichtigen. In diesem Beitrag wird ein Konzept vorgestellt, um das Potential des Eye-Trackings zur Erzeugung realitätsgetreuer, visueller Reize zu nutzen. Hierzu erfolgt die Betrachtung verschiedener Tiefenhinweise, die bei der Wahrnehmung im Nahbereich dominanten Einfluss besitzen und in bisherigen technischen Lösungen unzureichend angesprochen werden. Zusätzlich wird der Einfluss der Verzerrung der im HMD verbauten Linsen auf die Blickrichtungsabhängigkeit der Darstellung anhand eines Demonstrators zur Simulation von Linsenbrechung in HMDs aufgezeigt. Ausgehend von den beschriebenen Faktoren werden Lösungskonzepte präzisiert um die Einschränkungen zu überwinden. Der Beitrag endet mit einer Zusammenfassung sowie einem Ausblick auf nachfolgende Schritte zur Überwindung der Wahrnehmungsdiskrepanzen um ein realitätsgetreues, visuelles Nutzungserlebnis des Produkts zu ermögliche
Keywords: visuelle Wahrnehmung; Virtual Reality; Eye-Tracking; Head-Mounted-Display; User Experience

Natural Finger Interaction for CAD Assembly Modeling - Fechter, Marius; Wartzack, Sandro (ASME 2017 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, Volume 1: 37th Computers and Information in Engineering Conference, 2017)
In current CAD software the process of assembly modeling is hindered by a large number of separate rotation and translation actions necessary, especially in case of larger assemblies. Additionally matching faces, edges or points must be selected by clicking to define the appropriate constraint. In contrast to that, the process of assembling two normal sized physical parts in the real world seems to be rather simple. That is because we know how to grasp and move objects with our hands intuitively from our everyday experience. The idea behind this contribution is to enable the product developer to assemble CAD parts in a virtual environment through natural finger interaction like in reality. Therefore we present an overall method that combines the natural finger interaction with virtual objects and the insertion of constraints between rotationally symmetric CAD parts. The developed algorithms identify matching surfaces on the basis of the geometry as well as position and orientation of the parts in 3D space. This paper highlights the method to use a combination of real-time physics simulation and a heuristic approach to achieve an intuitive interaction interface. Additionally, we describe the detection algorithms developed to find assembly relationships between rotationally symmetric CAD parts without prior constraint definition. We also present a prototype system to demonstrate the functionality of the overall method. Furthermore, challenges for future research, such as extending the functionality of the detection algorithms on additional part types, like non-rotationally symmetric shapes, are discussed.
Keywords: Assembly Modeling; Computer-Aided Design; Virtual Reality; Natural User Interface